Impact of Work Skills, Performance, and Maintenance on Productivity: A Study on Head Truck Operators in PT. Terminal Petikemas Surabaya: Pengaruh Keterampilan Kerja, Kinerja, dan Pemeliharaan terhadap Produktivitas: Studi pada Operator Head Truck di PT. Terminal Petikemas Surabaya - Meyti Hanna Ester Kalangi; Indriana Kristiawati; Rizky Armando Ega Kusuma (Universitas Muhammadiyah Sidoarjo, 2023)
This scientific article investigates the relationship between work skills, performance, maintenance, and productivity in the context of head truck operations at PT. Terminal Petikemas Surabaya. The study, conducted through a descriptive research approach, involved a sample of 72 head truck operators. Multiple linear regression analysis was employed to examine the data. The results revealed a significant positive impact of work skills, performance, and maintenance on productivity. The regression model exhibited a high predictive capability, indicating that the variables of interest could be utilized to forecast productivity. The findings support the well-established understanding that individuals' work skills directly influence their level of productivity. Moreover, the study confirms the widely accepted notion that improved performance among head truck operators leads to enhanced output. Additionally, it highlights the significance of routine maintenance in increasing production levels. The implications of this research underscore the importance of investing in skill development, fostering optimal performance, and implementing effective maintenance practices to enhance productivity in head truck operations. Highlight: Work skills significantly influence productivity: The study reveals that the level of work skills directly impacts the productivity of head truck operators in PT. Terminal Petikemas Surabaya. Performance drives positive output: The findings confirm that the performance of head truck operators has a beneficial influence on their overall output. Routine maintenance enhances production: The research highlights the significance of regular maintenance of head trucks in contributing to increased productivity levels. Keyword: PT. Terminal Petikemas Surabaya, Head Truck Operators, Work Skills, Performance, Maintenance, Productivity